2020
DOI: 10.3389/feart.2020.00190
|View full text |Cite
|
Sign up to set email alerts
|

Schlieren-Bound Magmatic Structures Record Crystal Flow-Sorting in Dynamic Upper-Crustal Magma-Mush Chambers

Abstract: Multi-Scale Magma Flow-Sorting formed from the amalgamation of intruding magma pulses, and precludes dike, sill, or laccolith emplacement models. We conclude that schlieren-bound structures are faithful recorders of the multi-scale, hypersolidus evolution of upper-crustal magma bodies, and represent useful tools for studying plutonic systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 134 publications
(466 reference statements)
0
16
0
Order By: Relevance
“…In the Kuna Crest lobe, we have documented that early sheeting evolved within a few hundred thousand years, to larger, interacting crystal mush systems that represent active magma chambers. When U/Pb ages from our more extensive geochronologic study for the entire TIC are contoured (Memeti et al 2014;Paterson et al, 2016;Ardill et al, 2020b), broad regions (>hundreds of km 2 ) have similar ages and gradational internal contacts between distinct units, implying that it is quite permissible for these to represent magma chambers, a conclusion supported by thermal modeling (Yoshinobu et al, 1998;Paterson et al 2011;Karakas et al, 2017).…”
Section: Comparisons With Other Emplacement Modelsmentioning
confidence: 78%
See 3 more Smart Citations
“…In the Kuna Crest lobe, we have documented that early sheeting evolved within a few hundred thousand years, to larger, interacting crystal mush systems that represent active magma chambers. When U/Pb ages from our more extensive geochronologic study for the entire TIC are contoured (Memeti et al 2014;Paterson et al, 2016;Ardill et al, 2020b), broad regions (>hundreds of km 2 ) have similar ages and gradational internal contacts between distinct units, implying that it is quite permissible for these to represent magma chambers, a conclusion supported by thermal modeling (Yoshinobu et al, 1998;Paterson et al 2011;Karakas et al, 2017).…”
Section: Comparisons With Other Emplacement Modelsmentioning
confidence: 78%
“…Tobisch et al (2000) concluded that in the Ritter Range area "downward flow" of the host rocks occurred in the plutonic aureoles during emplacement. Several authors (e.g., Bateman and Chappell, 1979;Paterson, 2005, 2010;Paterson et al 2016;Ardill et al, 2020b) present evidence of internal emplacement processes of one pulse into another and document evidence of erosion and recycling of older units into younger pulses and downward flow of magma.…”
Section: Tuolumne Intrusive Complexmentioning
confidence: 99%
See 2 more Smart Citations
“…High proportion of water results in the fragmentation and fluidization of the rock even at low melt fraction (Fowler and Spera, 2008). We speculate that it might play a role in the formation of schlieren structures (Ardill et al, 2020). In case of chamber failure and eruption, the entrainment of those fragmented layers from the roof could explain the common presence of older crystals and the evidence for cold storage in volcanic product (Cooper and Kent, 2014;Rubin et al, 2017).…”
Section: Implications For Natural Systemsmentioning
confidence: 90%